Cultural Elements in a Malaysian English Language Textbook - Norhana Abdullah; Sanda Kumari D/O Chandran (2024)
'Culture' in L2 today is undoubtedly much more than teaching the great works of literature. It has made inroads into the fields of applied linguistics and second language education as well. Societal values, attitudes and cultural elements are integrated with the communicative approach to enhance the effectiveness of L2 acquisition Conversely, textbooks are an integral part of language learning in the classrooms. Although presently there is a deluge of alternative instructional materials, textbooks are still very much relevant in ascertaining the content, methods and approaches, educational philosophy, linguistic and cultural information in the classrooms. Hence, it is the intent of this paper to examine the cultural elements in a form four English language textbooks currently used in Malaysian ESL classrooms in order to determine the most prominent cultural dimension portrayed. A more specific and operational definition of culture which outlines four dimensions or ‘senses’ of culture; the aesthetic, sociological, semantic and the pragmatic posited by Adaskou, Britten & Fahsi (1990) is used to facilitate the investigation in this descriptive study. These aspects are representative of the myriad dimensions of culture as well as providing concrete substance to the abstractness of culture.